2014
DOI: 10.1016/j.jpsychores.2013.10.019
|View full text |Cite
|
Sign up to set email alerts
|

The combined association of depression and socioeconomic status with length of post-operative hospital stay following coronary artery bypass graft surgery: Data from a prospective cohort study

Abstract: ObjectiveTo understand the association between pre-operative depression symptoms, including cognitive and somatic symptom subtypes, and length of post-operative stay in patients undergoing coronary artery bypass graft (CABG) surgery, and the role of socioeconomic status (SES).MethodsWe measured depression symptoms using the Beck Depression Inventory (BDI) and household income in the month prior to surgery in 310 participants undergoing elective, first-time, CABG. Participants were followed-up post-operatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
77
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 33 publications
9
77
2
2
Order By: Relevance
“…Some sociodemographic characteristics presented by the participants of this study are similar to those of national and international studies of patients with coronary artery disease referred for CABG, such as: the prevalence of males, [11][12][13] presence of a partner, 11,12 low educational level, and age. 11 The results showed that the majority of participants did not practice physical activity, presented a history of angina, myocardial infarction, and arterial hypertension as comorbidities.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Some sociodemographic characteristics presented by the participants of this study are similar to those of national and international studies of patients with coronary artery disease referred for CABG, such as: the prevalence of males, [11][12][13] presence of a partner, 11,12 low educational level, and age. 11 The results showed that the majority of participants did not practice physical activity, presented a history of angina, myocardial infarction, and arterial hypertension as comorbidities.…”
Section: Discussionsupporting
confidence: 53%
“…14 Hypertension was also the most prevalent comorbidity presented by patients undergoing CABG in other studies. [11][12][13] The average BDI was 13.0, higher than the cutoff point for classifying the absence of depression and, at the same time, in the range established for classifying dysphoria. In another Brazilian study with 78 patients in the pre-CABG period, which had sociodemographic and clinical characteristics similar to those presented by the participants of this study, the mean BDI was less than nine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently have researchers begun to appreciate the information to be learned by considering both sets of factors simultaneously to better identify persons at elevated risk of poor cardiovascular outcomes and mortality 21, 23, 24, 25, 41. Whereas most prior work in this area has focused on the joint contributions of SES and a single psychosocial risk factor (eg, depression, stress), our research emphasized the importance of considering a confluence of psychosocial risk factors, in addition to SES, to identify those who are most vulnerable to CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence details the association between depression and poor recovery both in the immediate period following CABG surgery and in the longer term (Burg et al ., ; Saur et al ., ). Markers of short‐term recovery, including longer in‐hospital stay following surgery, pain, graft site and wound infection, have been linked with depression (Doering, Moser, Lemankiewicz, Luper, & Khan, ; Poole, Kidd et al ., ; Poole, Leigh et al ., ). Similarly, indices of long‐term recovery such as re‐hospitalization rates, future cardiac events, reductions in quality of life (QoL), and increased mortality have also been associated with depression (Blumenthal et al ., ; Connerney et al ., ).…”
Section: Introductionmentioning
confidence: 98%